The efficiency of vibration training on changes in strength - Katanic, B.; Milenkovic, D.; Ilic, P.; Vitasovic, M. (Sports Science and Health, 2020)
The study aim was to determine the effectiveness of vibration training on changes in strength in individuals of both sexes. Vibration training is a modern form of training that is becoming more and more widespread and frequent, and involves the application of vibrational stimulations of a certain form to cause functional and structural changes. It is used during strength training, where it can act in isolation on individual muscle regions or as whole body vibrational training. These observations provide an opportunity to apply a new method in training to improve the training itself and thus the performance of the athletes. The impact of this training on motor skills, and even strength, as one of the most studied areas, has not been extensively researched. This paper analyzes 14 studies on the effects of vibrational training on the change in power, and the papers are systematically analyzed. A review of research conducted in the field of this training shows that the effects of such training methods show in both professional and recreational athletes. In most of the studies analyzed, training has shown significant changes in power as well as in other motor skills.